Nickel hyperaccumulation is independent of the leaf economics spectrum, although it may be linked to plant water balance in an ultramafic plant community from Sabah (Malaysia) - Celestino Quintela-Sabarís; Michel-Pierre Faucon; Béatrice Gervais-Bergeron; Sukaibin Sumail; Antony van der Ent; Rimi Repin; John Sugau; Reuben Nilus; Thomas Rigaudier; Guillaume Echevarria; Sophie Leguédois (Plant and Soil, 2025)
Background and aims Nickel (Ni) hyperaccumulators are a group of plants able to store elevated amounts of this element in their leaves. Some studies indicate that hyperaccumulation may be associated with traits favouring fast resource capture or with traits favouring nutrient and water conservation, but there is no evidence for the role of nickel hyperaccumulation in the leaf economics spectrum. Our study aims to assess the differences in the leaf economics spectrum between Ni hyperaccumulators and non-hyperaccumulators. Methods We have conducted a field study involving five hyperaccumulators and ten non-hyperaccumulators growing on the same ultramafic community in Sabah (Malaysia). We measured two structural and seven chemical leaf traits and computed a Principal Component Analysis, which was complemented by a test of the phylogenetic signal of each trait and linear mixed models to assess the influence of each leaf trait on nickel accumulation. Results Our analyses inferred three principal components that reflected the main environmental constraints that shape the resource acquisition strategies of the studied ultramafic plant community: leaf economics spectrum, hyperaccumulation and water-use efficiency, and calcium to magnesium balance. Moreover, the linear mixed models indicated that carbon isotope discrimination and potassium concentrations had a significant effect on Ni accumulation, suggesting that nickel might replace partially potassium in its role in plant water balance. Conclusion Overall, the data suggest that in the community studied, Ni hyperaccumulation is independent of the leaf economics spectrum and related to plant water economy. More studies with other hyperaccumulator plants are needed to confirm these findings.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Bornean tropical forests recovering from logging at risk of regeneration failure - David C. Bartholomew; Robin Hayward; David F. R. P. Burslem; Paulo R. L. Bittencourt; Daniel Chapman; Mohd. Aminur Faiz Bin Suis; Reuben Nilus; Michael J. O'Brien; Glen Reynolds; Lucy Rowland; Lindsay F. Banin; Daisy Dent (Global Change Biology, 2024)
Active restoration through silvicultural treatments (enrichment planting, cutting climbers and liberation thinning) is considered an important intervention in logged forests. However, its ability to enhance regeneration is key for long‐term recovery of logged forests, which remains poorly understood, particularly for the production and survival of seedlings in subsequent generations. To understand the long‐term impacts of logging and restoration we tracked the diversity, survival and traits of seedlings that germinated immediately after a mast fruiting in North Borneo in unlogged and logged forests 30–35 years after logging. We monitored 5119 seedlings from germination for ~1.5 years across a mixed landscape of unlogged forests (ULs), naturally regenerating logged forests (NR) and actively restored logged forests via rehabilitative silvicultural treatments (AR), 15–27 years after restoration. We measured 14 leaf, root and biomass allocation traits on 399 seedlings from 15 species. Soon after fruiting, UL and AR forests had higher seedling densities than NR forest, but survival was the lowest in AR forests in the first 6 months. Community composition differed among forest types; AR and NR forests had lower species richness and lower evenness than UL forests by 5–6 months post‐mast but did not differ between them. Differences in community composition altered community‐weighted mean trait values across forest types, with higher root biomass allocation in NR relative to UL forest. Traits influenced mortality ~3 months post‐mast, with more acquisitive traits and relative aboveground investment favoured in AR forests relative to UL forests. Our findings of reduced seedling survival and diversity suggest long time lags in post‐logging recruitment, particularly for some taxa. Active restoration of logged forests recovers initial seedling production, but elevated mortality in AR forests lowers the efficacy of active restoration to enhance recruitment or diversity of seedling communities. This suggests current active restoration practices may fail to overcome barriers to regeneration in logged forests, which may drive long‐term changes in future forest plant communities.

Multi-stemming enhances tree survival and growth in Borneo’s logged forests - Jakub Kvasnica; Radim Matula; Martin Rejžek; Robert M. Ewers; Terhi Riutta; Edgar C. Turner; Reuben Nilus; Martin Svátek (Forest Ecology and Management, 2023)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Incorporating connectivity into conservation planning for the optimal representation of multiple species and ecosystem services - Sara H. Williams; Sarah A. Scriven; David F. R. P. Burslem; Jane K. Hill; Glen Reynolds; Agnes L. Agama; Frederick Kugan; Colin R. Maycock; Eyen Khoo; Alexander Y. L. Hastie; John B. Sugau; Reuben Nilus; et al. (Conservation Biology, 2020)
Conservation planning tends to focus on protecting species’ ranges or landscape connectivity but seldom both—particularly in the case of diverse taxonomic assemblages and multiple planning goals. Therefore, information on potential trade‐offs between maintaining landscape connectivity and achieving other conservation objectives is lacking. We developed an optimization approach to prioritize the maximal protection of species’ ranges, ecosystem types, and forest carbon stocks, while also including habitat connectivity for range‐shifting species and dispersal corridors to link protected area. We applied our approach to Sabah, Malaysia, where the state government mandated an increase in protected‐area coverage of approximately 305,000 ha but did not specify where new protected areas should be. Compared with a conservation planning approach that did not incorporate the 2 connectivity features, our approach increased the protection of dispersal corridors and elevational connectivity by 13% and 21%, respectively. Coverage of vertebrate and plant species’ ranges and forest types were the same whether connectivity was included or excluded. Our approach protected 2% less forest carbon and 3% less butterfly range than when connectivity features were not included. Hence, the inclusion of connectivity into conservation planning can generate large increases in the protection of landscape connectivity with minimal loss of representation of other conservation targets.

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

Recovery of ultramafic soil functions and plant communities along an age-gradient of the actinorhizal tree Ceuthostoma terminale (Casuarinaceae) in Sabah (Malaysia) - Celestino Quintela-Sabarís; Etienne Auber; Sukaibin Sumail; Jean-François Masfaraud; Michel-Pierre Faucon; Françoise Watteau; Ramez F. Saad; Antony van der Ent; Rimi Repin; John Sugau; Reuben Nilus; Guillaume Echevarria; et al. (Plant and Soil, 2019)

Topography shapes the structure, composition and function of tropical forest landscapes - Tommaso Jucker; Boris Bongalov; David F. R. P. Burslem; Reuben Nilus; Michele Dalponte; Simon L. Lewis; Oliver L. Phillips; Lan Qie; David A. Coomes (Ecology Letters, 2018)
Topography is a key driver of tropical forest structure and composition, as it constrains local nutrient and hydraulic conditions within which trees grow. Yet, we do not fully understand how changes in forest physiognomy driven by topography impact other emergent properties of forests, such as their aboveground carbon density ( ACD ). Working in Borneo – at a site where 70‐m‐tall forests in alluvial valleys rapidly transition to stunted heath forests on nutrient‐depleted dip slopes – we combined field data with airborne laser scanning and hyperspectral imaging to characterise how topography shapes the vertical structure, wood density, diversity and ACD of nearly 15 km 2 of old‐growth forest. We found that subtle differences in elevation – which control soil chemistry and hydrology – profoundly influenced the structure, composition and diversity of the canopy. Capturing these processes was critical to explaining landscape‐scale heterogeneity in ACD , highlighting how emerging remote sensing technologies can provide new insights into long‐standing ecological questions.

Variation in the aboveground stand structure and fine-root biomass of Bornean heath (kerangas) forests in relation to altitude and soil nitrogen availability - Kazuki Miyamoto; Rota Wagai; Shin-ichiro Aiba; Reuben Nilus (Trees, 2016)

Large trees drive forest aboveground biomass variation in moist lowland forests across the tropics - J. W. Ferry Slik; Gary Paoli; Krista McGuire; Ieda Amaral; Jorcely Barroso; Meredith Bastian; Lilian Blanc; Frans Bongers; Patrick Boundja; Connie Clark; Murray Collins; Gilles Dauby; et al. (Global Ecology and Biogeography, 2013)
Aim Large trees (d.b.h. ≥ 70 cm) store large amounts of biomass. Several studies suggest that large trees may be vulnerable to changing climate, potentially leading to declining forest biomass storage. Here we determine the importance of large trees for tropical forest biomass storage and explore which intrinsic (species trait) and extrinsic (environment) variables are associated with the density of large trees and forest biomass at continental and pan‐tropical scales. Location Pan‐tropical. Methods Aboveground biomass ( AGB) was calculated for 120 intact lowland moist forest locations. Linear regression was used to calculate variation in AGB explained by the density of large trees. Akaike information criterion weights ( AICc ‐wi) were used to calculate averaged correlation coefficients for all possible multiple regression models between AGB /density of large trees and environmental and species trait variables correcting for spatial autocorrelation. Results Density of large trees explained c . 70% of the variation in pan‐tropical AGB and was also responsible for significantly lower AGB in Neotropical [287.8 (mean) ± 105.0 ( SD ) M g ha −1 ] versus Palaeotropical forests (Africa 418.3 ± 91.8 M g ha −1 ; Asia 393.3 ± 109.3 M g ha −1 ). Pan‐tropical variation in density of large trees and AGB was associated with soil coarseness (negative), soil fertility (positive), community wood density (positive) and dominance of wind dispersed species (positive), temperature in the coldest month (negative), temperature in the warmest month (negative) and rainfall in the wettest month (positive), but results were not always consistent among continents. Main conclusions Density of large trees and AGB were significantly associated with climatic variables, indicating that climate change will affect tropical forest biomass storage. Species trait composition will interact with these future biomass changes as they are also affected by a warmer climate. Given the importance of large trees for variation in AGB across the tropics, and their sensitivity to climate change, we emphasize the need for in‐depth analyses of the community dynamics of large trees.

Herbivory of tropical rain forest tree seedlings correlates with future mortality - Markus P. Eichhorn; Reuben Nilus; Stephen G. Compton; Sue E. Hartley; David F. R. P. Burslem (Ecology, 2010)
Tree seedlings in tropical rain forests are subject to both damage from natural enemies and intense interspecific competition. This leads to a trade‐off in investment between defense and growth, and it is likely that tree species specialized to particular habitats tailor this balance to correspond with local resource availability. It has also been suggested that differential herbivore impacts among tree species may drive habitat segregation, favoring species adapted to particular resource conditions. In order to test these predictions, a reciprocal transplant experiment in Sabah, Malaysia, was established with seedlings of five species of Dipterocarpaceae. These were specialized to either alluvial ( Hopea nervosa , Parashorea tomentella ) or sandstone soils ( Shorea multiflora , H. beccariana ), or were locally absent ( S. fallax ). A total of 3000 seedlings were planted in paired gap and understory plots in five sites on alluvial and sandstone soils. Half of all seedlings were fertilized. Seedling growth and mortality were recorded in regular samples over 3.5 years, and rates of insect herbivore damage were estimated from censuses of foliar tissue loss on marked mature leaves and available young leaves. Greater herbivory rates on mature leaves had no measurable effects on seedling growth but were associated with a significantly increased likelihood of mortality during the following year. In contrast, new‐leaf herbivory rates correlated with neither growth nor mortality. There were no indications of differential impacts of herbivory among the five species, nor between experimental treatments. Herbivory was not shown to influence segregation of species between soil types, although it may contribute toward differential survival among light habitats. Natural rates of damage were substantially lower than have been shown to influence tree seedling growth and mortality in previous manipulative studies.

Environmental correlates of tree biomass, basal area, wood specific gravity and stem density gradients in Borneo's tropical forests - J. W. F. Slik; Shin‐Ichiro Aiba; Francis Q. Brearley; Chuck H. Cannon; Olle Forshed; Kanehiro Kitayama; Hidetoshi Nagamasu; Reuben Nilus; John Payne; Gary Paoli; Axel D. Poulsen; Niels Raes; et al. (Global Ecology and Biogeography, 2010)
Aim Tropical forests have been recognized as important global carbon sinks and sources. However, many uncertainties about the spatial distribution of live tree above‐ground biomass (AGB) remain, mostly due to limited availability of AGB field data. Recent studies in the Amazon have already shown the importance of large sample size for accurate AGB gradient analysis. Here we use a large stem density, basal area, community wood density and AGB dataset to study and explain their spatial patterns in an Asian tropical forest. Location Borneo, Southeast Asia. Methods We combined stem density, basal area, community wood density and AGB data from 83 locations in Borneo with an environmental database containing elevation, climate and soil variables. The Akaike information criterion was used to select models and environmental variables that best explained the observed values of stem density, basal area, community wood density and AGB. These models were used to extrapolate these parameters across Borneo. Results We found that wood density, stem density, basal area and AGB respond significantly, but differentially, to the environment. AGB was only correlated with basal area, but not with stem density and community wood specific gravity. Main conclusions Unlike results from Amazonian forests, soil fertility was an important positive correlate for AGB in Borneo while community wood density, which is a main driver of AGB in the Neotropics, did not correlate with AGB in Borneo. Also, Borneo's average AGB of 457.1 Mg ha −1 was c . 60% higher than the Amazonian average of 288.6 Mg ha −1 . We find evidence that this difference might be partly explained by the high density of large wind‐dispersed Dipterocarpaceae in Borneo, which need to be tall and emergent to disperse their seeds. Our results emphasize the importance of Bornean forests as carbon sinks and sources due to their high carbon storage capacity.

The Value of Rehabilitating Logged Rainforest for Birds - DAVID P. EDWARDS; FELICITY A. ANSELL; ABDUL H. AHMAD; REUBEN NILUS; KEITH C. HAMER (Conservation Biology, 2009)
The recent advent of carbon crediting has led to a rapid rise in biosequestration projects that seek to remove carbon from the atmosphere through afforestation and forest rehabilitation. Such projects also present an important potential opportunity to reverse biodiversity losses resulting from deforestation and forest degradation, but the biodiversity benefits of different forms of biosequestration have not been considered adequately. We captured birds in mist nets to examine the effects of rehabilitation of logged forest on birds in Sabah, Borneo, and to test the hypothesis that rehabilitation restores avian assemblages within regenerating forest to a condition closer to that seen in unlogged forest. Species richness and diversity were similar in unlogged and rehabilitated forest, but significantly lower in naturally regenerating forest. Rehabilitation resulted in a relatively rapid recovery of populations of insectivores within logged forest, especially those species that forage by sallying, but had a marked adverse effect on frugivores and possibly reduced the overall abundance of birds within regenerating forest. In view of these results, we advocate increased management for heterogeneity within rehabilitated forests, but we strongly urge an increased role for forest rehabilitation in the design and implementation of a biodiversity‐friendly carbon‐offsetting market.

Liana habitat associations and community structure in a Bornean lowland tropical forest - Saara J. DeWalt; Kalan Ickes; Reuben Nilus; Kyle E. Harms; David F. R. P. Burslem (Plant Ecology, 2006)